(untitled) (Ameghiniana, 2003)
In this paper the first descriptive data on a Lower Cretaceous frog just discovered in province of Salta, N.W. Argentine, are given. The author proposes a new genus and species, Saltenia ibafiezi, for this frog. It is a small anuran with eight presacral vertebrae, quite probably procoelous; with three pairs of free ribs; urostyle fused with a sacral vertebra with moderately expanded ends; shoulder girdle quite probably arciferous with rod-like coracoid and clavicle bent forward;· with the skull longer than wide, with the quadrate in a line anterior to that of the condiles, frontoparietals fused and quadratojugal normaly developed. The comparison between both modern and extinct Anura seems to indicate the possibility that Saltenia .may belong to the suborden Aglossa